Educational leadership and reform - Hoy, Wayne K.; Miskel, Cecil G. (Emerald Publishing Limited : Information Age Publishing, 2005)
This book is the fourth in a series on research and theory dedicated to advancing our understanding of schools through empirical study and theoretical analysis. Scholars, both young and established, are invited to publish original analyses, but we especially encourage young scholars to contribute to this series. The current volume is similar to its predecessors in that it provides a mix of beginning and established scholars and a broad range of theoretical perspectives; in all, 27 authors contributed to 13 separate analyses, which were selected for publication this year. The chapters also provide a mix of methodologies including experimental, survey, case studies, selfanalysis, multilevel modeling, and structural equation modeling.
Keywords: Educational leadership -- United States.; Educational change -- United States.; School management and organization -- United States.; Education -- Educational Policy & Reform -- General.; Educational strategies and policy: inclusion.; Educational strategies and policy.; elektronické knihy; electronic books